Tinjauan Yuridis Dampak Overclaim Kosmetik terhadap Konsumen - Maulida, Ersha; Abdi, Muhammad Mahendra; Nofrizal, Deni (LPPM Institut Pendidikan Nusantara Global, 2025)
The phenomenon of increasing circulation of cosmetic products that do not meet standards and the rampant practice of overclaims have caused serious concerns for consumers, both in terms of health and economy. This situation demands the presence of a strict legal system and effective supervisory mechanisms to ensure the security and clarity of product information circulating in the market. This study uses a normative juridical approach to examine various sources of law, literature, and regulations that govern the cosmetics industry in Indonesia. The main focus of the research is directed at the analysis of forms of legal protection for consumers against cosmetic products that convey unrealistic claims. In its discussion, this study highlights the important role of Law Number 8 of 1999 concerning Consumer Protection and BPOM Regulation Number 12 of 2020 concerning Procedures for Submitting Cosmetic Notifications as the main legal instrument in ensuring product transparency and safety. The findings show that although the legal framework is adequate, its implementation still faces obstacles, especially due to the rise of illegal cosmetics on online platforms and conventional markets. Therefore, strengthening regulations, consumer education, and continuous supervision are important steps to ensure optimal legal protection for the public.